Tuning quantum heat transport in magnetic nanostructures by spin-phonon interaction. (1st May 2022) - Pan, Hui; Ding, Zhong-Ke; Zeng, Yu-Jia; Li, Qiu-Qiu; Tang, Li-Ming; Chen, Ke-Qiu
Abstract: The introduction of spin degree of freedom has not only made the electronic transport properties colorful, but also highly attracted people's attention to the spin-related quantum heat transport, with the rapid progress of spin caloritronics in recent year. Against this background, the modeling and tuning of quantum heat transport in magnetic nanostructures has become an emerging and attractive topic. In particular, the spin-phonon interaction has played a crucial role in the novel transport behaviors of heat and spin. In this perspective article, we give an insight into the current theoretical and experimental progresses and discuss the further research perspectives of spin-phonon interaction-related heat transfer.